Exploring the involvement of gut microbiota in cancer therapy-induced cardiotoxicity - Kunika; Frey, Norbert; Rangrez, Ashraf Yusuf (International journal of molecular sciences, 2023)
Trillions of microbes in the human intestinal tract, including bacteria, viruses, fungi, and protozoa, are collectively referred to as the gut microbiome. Recent technological developments have led to a significant increase in our understanding of the human microbiome. It has been discovered that the microbiome affects both health and the progression of diseases, including cancer and heart disease. Several studies have indicated that the gut microbiota may serve as a potential target in cancer therapy modulation, by enhancing the effectiveness of chemotherapy and/or immunotherapy. Moreover, altered microbiome composition has been linked to the long-term effects of cancer therapy; for example, the deleterious effects of chemotherapy on microbial diversity can, in turn, lead to acute dysbiosis and serious gastrointestinal toxicity. Specifically, the relationship between the microbiome and cardiac diseases in cancer patients following therapy is poorly understood. In this article, we provide a summary of the role of the microbiome in cancer treatment, while also speculating on a potential connection between treatment-related microbial changes and cardiotoxicity. Through a brief review of the literature, we further explore which bacterial families or genera were differentially affected in cancer treatment and cardiac disease. A deeper understanding of the link between the gut microbiome and cardiotoxicity caused by cancer treatment may help lower the risk of this critical and potentially fatal side effect.